Polypharmacy and deprescribing in people with learning disabilities. (2nd June 2019) - Adams, Danielle
Abstract : In order to effectively manage problematic polypharmacy and stop medicines safely, it is imperative that there is an appreciation of all the factors that are involved in the deprescribing process. A collaborative, patient-centred approach is required to optimise medicines effectively and reduce inappropriate prescribing. Patients should be equal stakeholders in this process. Implementing shared decision-making, while considering the issues of capacity and consent, may contribute to improved patient empowerment and outcomes. Reflecting on the risks of deprescribing — such as the implications of relapse, and the reduction of beneficial side effects and the risk of medication errors — can provide a framework for positive patient outcomes. Key to managing these risks is effective communication between all stakeholders. The STOMP campaign is addressing the overprescribing of psychotropic medicines in people with learning disabilities. It is hoped that by reducing these medicines, in the absence of a mental health diagnosis, existing health inequalities, morbidity and mortality may be reduced.